Konsep Pengembangan Kurikulum Pendidikan Agama Islam (PAI) dI MTs Persis Sadang - Abas, Heri Mulyadi; Sumpena, Maman (Sekolah Tinggi Agama Islam (STAI) Al Hidayah Tasikmalaya, 2025)
This study aims to analyze the Islamic Religious Education (PAI) curriculum development model at MTs Persis Sadang and its implementation strategy. The approach used is qualitative with descriptive methods, through interviews, participatory observation, and document review. The results showed that curriculum development in this madrasah uses a participatory or collaborative curriculum model, in which the Curriculum Development Team (TPK) prepares a draft curriculum that is discussed, socialized, ratified, and implemented. MTs Persis Sadang adapts the Ministry of Religious Affairs curriculum with the distinctive curriculum of Jam'iyyah Persis, creating a unique education system. The learning load is lighter than the curriculum of jam'iyyah Persis but greater than the Ministry of Religion's curriculum, so that students can learn optimally. The PAI material is broader and more in-depth than the government standard. The recommendations of this study emphasize the need for periodic evaluation to ensure the balance between the pesantren curriculum and the national curriculum, as well as strengthening the implementation strategy to be more effective in achieving the madrasah vision.